Natural Products Obtained from Argentinean Native Plants Are Fungicidal against Citrus Postharvest Diseases - Alvarez, Norma Hortensia (2023)
Natural products obtained from plants constitute an alternative to chemically synthesized fungicides, whose improper use might have caused the development of resistant fungal strains. In the present work, 40 products obtained from 20 native Argentinean plant species were tested against three citrus postharvest pathogens: Penicillium digitatum, Penicillium italicum, and Geotrichum citri-aurantii. Natural products were obtained by classical solvent extraction methods and the fungicidal evaluation was carried out by agar diffusion tests using commercial fungicides as negative controls and dimethyl sulfoxide as a positive one. The inhibition percentages were determined 7 and 14 days post inoculation of each fungus. Most of the products tested showed inhibition percentages higher than 50% for G. citri-aurantii, but only 20% of them were active against P. digitatum and P. italicum. The most promising products which inhibited (100%) the growth of at least one of the three phytopathogens were extracted from the following plants: Orthosia virgata, Petiveria alliacea, Funastrum clausum, Solanum caavurana, and Solanum pilcomayense. These products were tested over inoculated oranges and there were no statistically significant differences between the treatments with a commercial fungicide and the methanolic extract in the control of fruit rot. The products extracted from native plants have fungicide potential, but further studies are required.